Would the creation of industrial park and the industrialisation of Pasir Gudang creates opportunities for property developers in the area. / Bhadariah Mohd. Salleh - Mohd. Salleh, Bhadariah (2002)
Industrialisation of an area would create a new township, either the area itself of the neighbouring area. Penang, for instance has totally turned itself from depending on the trading and tourism to evolve itself to manufacturing hub. The industrialisation program in Pulau Pinang started when the Country first Free Trade Zone was set up in the 1970s. The concentration on industrialisation has opened up many residential estates and the place is one of the most congested with population in the country. Pasir Gudang, on the other hand, set-up its own free trade zone in the 1984 and the place have created more than 60,000 jobs since its opening. These jobs have brought influx of people from all over the country. But differ from Penang or Shah Alam, the property business here is not as encouraging. The slow sales and the lack of response reported in the dailies brought the question on why the people turned away to other place when looking for houses. For this research, the focus is on the people who renting out flats. Variables that have been identified as the independent to the demand of houses here would be the infrastructure, facilities and amenities, employment opportunities and the population itself. The research conducted, identified the locality of the residents and their intention of staying might affect the demand for housing. It also reveal that the nature of the factory worker that make up the majority of the resident here, come from identical income bracket and this group is the most price sensitive buyers. It is also found that due to the nature of products produced here, which includes chemical and petrochemical, make the people wary of staying for a long period or permanently.